Evolutionary history of Nile perch Lates sp. inferred from mitochondrial DNA variation analyses - Mwanja, Matthew T.; Muwanika, Vincent B.; Masembe, Charles; Nyakaana, Silvester; Waiswa Mwanja, Wilson (Zoological Studies, 2013)
Evolutionary histories of aquatic species are often characterized by distinct patterns of genetic variation, which in part reflect drainage evolution. In the present study, the consequences of paleo-environmental changes on patterns of genetic variation of the mitochondrial DNA control region in Nile perch Lates sp. sampled from seven water bodies across the African continent were investigated. Results: In a total sample of 124 individual sequences, 37 distinct haplotypes were observed, and 78.4% of these haplotypes were location specific. Haplotypes were found to cluster into two major groups, one composed of individuals sampled from East Africa and another from West Africa, with no haplotypes shared in between. Conclusion: These lineages may have developed in geographical isolation during the Pleistocene and have remained largely allopatric without gene flow (Nm = 0.0) since that time. There was also evidence that both of these genetic lineages have undergone recent population expansions. We interpret these results in light of the recent evolution of Africa's modern drainage network.
Keywords: Africa drainage system; Nile perch; Evolution; mtDNA